Photovoltaic Technology and Electricity Saving Strategies for Fixed-Velocity-Measuring System - ZhangLi Lan; Jian Li (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
The power supply methods for fixed-velocity-measuring system (FVMS) based on photovoltaic (PV) technology are proposed after analysis and comparison among the current methods for FVMS on freeway. According to the sunshine condition in typical low sunshine areas, all components consist of PV system are specially designed, including the related maximum power point track (MPPT) technology for solar panel and the charge-discharge algorithm for storage battery in the dedicated controller. Targeted electricity saving strategies for FVMS on freeway are put forward. Experimental results show high efficiency and stability of the dedicated controller and in practical application, the specially designed PV system in this paper can provide continuous electric power supply throughout a year in an efficient way, and the output voltage and frequency are stable. DOI : http://dx.doi.org/10.11591/telkomnika.v12i6.5477